The contribution of optimal turbo fan transport aircraft climb schedule to air company economy - Mirosavljević, Petar; Gvozdenović, Slobodan; Čokorilo, Olja (Technological and Economic Development of Economy, 2009)
Today airlines are challenging two opposite goals: minimization of flight fuel consumption and minimization of elapsed flight time. A well‐known cost structure and cost generators represent significant pre‐conditions for defining cost optimization strategy in an airline company. Airline company management has a limited set of tools for cost managing, which include the following documents: Performance Engineers’ Manual and Aircraft Flight Manual. In this particular paper review we discuss the problem of vertical flight path of turbo‐fan aircraft, where we point out the impact of the choice of climb technique on the overall en route flight profile costs. In temporary aircraft flight preparation process, there is no stressing out the significance of the climb phase in minimizing costs of this particular flight phase. In the paper we show the procedure of defining optimal climbing resulting minimum costs, but also optimal function operational adjustment to the climb schedule. This way of the approximation of optimal function and its adjustment to the operational use enables the application of minimal cost climbing technique in operational use of transportation aircraft. On short‐haul flights, climb phase can reduce cruise flight length up to 60% of total range. In the paper, we show the impact of climb regime on flight profile of turbo‐fan aircraft considering the usage of time, fuel and costs. The impact is shown according to the data taken from the Performance Engineers Manual. The impact stresses the importance of minimum costs climbing regime to cutting down total flight costs. It also shows the conditions which need to be fulfilled in order to apply minimum costs climbing technique. We identify the scope of CAS speed during climb and TOC for flights minimum total expenses by using minimum costs climbing technique. Conditions for achieving minimum costs climbing technique are the results of the logarithmic differential. In order to achieve optimal numerical results we used Newton‐Raphson formula. Turbosraigtinio transporto lėktuvo optimalaus kilimo plano poveikis oro bendrovei Santrauka. Šiandien oro transporte svarbūs du tikslai: skrydžio metu sunaudojamo kuro mažinimas ir skrydžio laiko trumpinimas. Žinoma kainos struktūra ir kainos komponentės yra reikšmingos išankstinės sąlygos, padedančios sudaryti kainos optimizavimo strategiją oro transporto bendrovėje. Oro transporto bendrovės valdytojai turi ribotą sąnaudų valdymo priemonių komplektą – tai „Priežiūros inžinieriaus vadovas“ ir „Orlaivio skrydžio vadovas“. Straipsnyje aptariama turbosraigtinio lėktuvo vertikalios skrydžio krypties problema, parodomas pasirinktos kilimo technikos poveikis bendrai skrydžio kainai. Dabartiniame lėktuvo ruošimosi skrydžiui procese nėra pabrėžiama kilimo fazės įtaka bendrų skrydžio sąnaudų mažinimui. Straipsnyje pateikiama procedūra, kaip nustatyti optimalų orlaivio kilimą mažiausiomis sąnaudomis, taip pat optimalumo funkcijos korekciją kilimo plane. Optimalumo funkcijos aproksimavimas ir jos naudojimas leidžia taikyti mažiausių sąnaudų kilimo techniką lėktuve. Trumpalaikiuose skrydžiuose kilimo fazė gali sumažinti kruizinio skrydžio trukmę iki 60 proc. Straipsnyje rodoma, kaip lėktuvo kilimo režimas daro poveikį turbosraigtinio lėktuvo skrydžiui laiko, kuro ir sąnaudų požiūriu remiantis duomeni mis, paimtais iš „Priežiūros inžinieriaus vadovo“. Skaičiai rodo, kaip minimalių sąnaudų kilimo režimas sumažina bendrąsias skrydžio sąnaudas. Straipsnyje taip pat atskleidžiamos sąlygos, kurios turi būti vykdytos norint pritaikyti minimalių sąnaudų kilimo techniką. Ją naudojant nustatytas lėktuvo skrydžio greitis ir pakilimo aukštis. Minimalių sąnaudų kilimo technikos sąlygos yra logaritminio diferencialo prendiniai. Optimaliems skaitmeniniams rezultatams gauti panaudota Niutono ir Rapsono formulė. Reikšminiai žodžiai: oro bendrovė, ekonomija, transporto lėktuvas, kilimas, techniniai duomenys, optimizavimas, sąnaudos. First published online: 21 Oct 2010